Digital transformation as a catalyst for green innovation: An Examination of high-tech enterprises in China's Yangtze River Delta - Qin Zhu; Shi-Zheng Huang; Somjintana Koompai (Sustainable Futures)
Green innovation represents a foundational strategy for companies aiming for sustainable and superior growth. In the digital economy landscape, rapid advancements in digital technologies provide enterprises with renewed momentum for progression. Nevertheless, there is scant empirical evidence supporting its efficacy in enhancing environmentally responsible corporate innovation. In the present study, utilising the resource-based view, data were gathered from 571 high-tech firms in China's Yangtze River Delta via surveys. Through hierarchical regression analysis, the interaction between digital transformation and green innovation was examined, taking into account the moderating effect of market-driven environmental pressures. The results indicate that digital transformation substantially promotes green innovation, and this relationship is further positively affected by the presence of market-driven environmental pressures. The present research contributes to the enhancement of green innovation theories and broadens the scope of digitalization research, providing valuable insights for advancing a green, low-carbon circular economy in the digital context.